1972
DOI: 10.1139/f72-074
|View full text |Cite
|
Sign up to set email alerts
|

Mating Behavior in the Spider Crab, Chionoecetes opilio

Abstract: During the week-long precopulatory embrace, the male spider crab, Chionoecetes opilio, held the female, even when attacking intruding males. Before a 45-min copulation period the male assisted female ecdysis. During the postcopulatory embrace spermatophores flowed onto the pleopods of the female. Polygamous males as small as 60 mm width mated with larger females. More than one fertile egg batch was frequently produced from one mating. Females mated successfully up to 95 hr after molting. Hard-shelled females s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 0 publications
2
38
2
Order By: Relevance
“…The position of intermediate size-classes (60-75 mm) on the factorial plane implies that these carapace widths were represented in similar proportions in all samples. From the growth model proposed by Watson (1969) for snow crabs, animals with carapace width around 75 mm correspond to immediate prerecruits (one molt before being recruited to the fishery). It follows that these prerecruits have a wide bathymetric distribution in shallow areas as well as on the fishing grounds at greater depths.…”
Section: Research Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…The position of intermediate size-classes (60-75 mm) on the factorial plane implies that these carapace widths were represented in similar proportions in all samples. From the growth model proposed by Watson (1969) for snow crabs, animals with carapace width around 75 mm correspond to immediate prerecruits (one molt before being recruited to the fishery). It follows that these prerecruits have a wide bathymetric distribution in shallow areas as well as on the fishing grounds at greater depths.…”
Section: Research Surveysmentioning
confidence: 99%
“…If the existence of spring recruitment and summer growth periods fits the belief of most authors about snow crab growth, the evidence for a second recruitment period remains unexplained. To explain the observed variations in the catch-per-unit-effort, Lamoureux assumed that prerecruits are able to molt twice a year instead of once, as proposed by Watson (1969). The first molt in winter would induce recruitment before the fishing season and the second molt in summer would induce autumn recruitment.…”
Section: Implications For Management Of the Stockmentioning
confidence: 99%
“…(4) Reproductive behaviors are complex. Males are polygamous and may guard females before (Watson 1972) and after (Sainte-Mane et al 1997) copulation. Pubescent females attract males by way of pheromones (Bouchard et al 1996) and, once molted, can copulate several times shortly before and after extruding their eggs with the same male (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Copulation Copulation takes place during a period when adults at their 11th molting stage and just past ecdysis still have a soft carapace (Kon and Nanba, 1968a;Watson, 1970Watson, , 1972. Thus, the seminal receptacle of males that have attained their 10th molting stage contains no spermatozoa (Kon and Honma (1970a).…”
Section: Copulation Spawning and Incubationmentioning
confidence: 99%
“…Furthermore, their seminal receptacle always contains spermatozoa (Kon and Honma (1970a) so that copulation does not seem to be necessary for them. In fact, experimental feeding of sample adult females collected, indicated that no copulation took place once the fertilised eggs held in the pleopods were hatched (Kon, 1976;Watson, 1972 Copulatory and spawning behavior observed between the 10th and 11th molting stages indicate that the same individuals reared experimentally for five years produced normal, fertilised eggs until the fourth spawning even though they did not engage in copulation any more after the second spawning (Kobayashi, 1983). Paul (1982) who reared adult C. bairdi females, reported:…”
Section: Copulation Spawning and Incubationmentioning
confidence: 99%